Transcriptome Sequencing Identifies Abnormal lncRNAs and mRNAs and Reveals Potentially Hub Immune-Related mRNA in Osteoporosis with Vertebral Fracture - Sun R; Duan D; Li R (Clinical Interventions in Aging, 2024)
Rongxin Sun,1 Desheng Duan,2 Renzeng Li2 1Department of Orthopaedics, The Sixth Affiliated Hospital of Xinjiang Medical University, Urumqi, Xinjiang Province, People’s Republic of China; 2Second Department of Orthopaedics, Third People’s Hospital of Anyang City, Anyang City, Henan Province, People’s Republic of ChinaCorrespondence: Renzeng Li, Second Department of Orthopaedics, Third People’s Hospital of Anyang City, 363 Dongfeng Road, Beiguan District, Anyang City, Henan Province, People’s Republic of China, Tel +86-13837247813, Email LRZ_doctor@163.comBackground: Recent studies have put forward the viewpoint of “bone immunology”, which holds that the immune system and immune factors play an important regulatory role in the occurrence and development of osteoporosis. This study was intended to identify genetic characteristics of differentially expressed immune-related mRNA and lncRNA in patients combined with osteoporosis and vertebral fracture.Methods: The peripheral blood samples were obtained from 3 groups of subjects: healthy control (HC), osteoporosis patients without vertebral fracture (OWF), and osteoporosis patients combined with vertebral fracture (OVF). The data were integrated to obtain differentially expressed mRNAs (DEmRNAs) and differentially expressed lncRNAs (DElncRNAs). Subsequently, the protein-protein interaction (PPI) networks were constructed. Gene Ontology (GO) and Kyoto Encyclopaedia of Genes and Genomes (KEGG) enrichment analyses were performed. Cytoscape-cytoHubba plug-in was used to identify key DEmRNAs. Furthermore, lncRNA-miRNA-mRNA, mRNA-lncRNA co-expression and transcription factors (TFs) networks were constructed. In addition, real-time PCR verification was performed.Results: Totally of 3378 lncRNA-mRNA pairs were obtained, and the lncRNA co-expressed mRNA was mainly enriched in immune-related pathways, especially in GO-biological process (GO-BP) analysis. A total of 8 hub immune-related DEmRNAs were obtained, including IL18R1, IL18RAP, SLC11A1, CSF2RA, CCR3, IL1R2, PGLYRP1, and IL1R1. The TFs network showed that 8 hub immune-related DEmRNAs had interacting TFs. The co-expression network showed that 7 hub immune-related DEmRNAs (IL18R1, IL18RAP, SLC11A1, CSF2RA, IL-1R2, PGLYRP1, and IL1R1) had lncRNA-mRNA co-expression relationship. In addition, the lncRNA-miRNA-mRNA network includes 32 miRNAs, 7 hub immune-related mRNAs (IL18R1, IL18RAP, CSF2RA, CCR3, IL1R2, PGLYRP1, and IL1R1), and 11 lncRNAs.Conclusion: Our study provides a novel and in-depth identification of co-expressed mRNAs and lncRNAs in patients combined with osteoporosis and vertebral fracture at a molecular level. This may provide new candidate biomarkers for the diagnosis of patients with high-risk fractures in the future.Keywords: osteoporosis, vertebral fracture, immune, mRNA, lncRNA, transcriptome